Culturally Appropriate Interventions For Prevention And Treatment Of Mental Health In Saudi Arabia (Journal of Namibian Studies : History Politics Culture, 2022)
Mental health conditions present devastating effects to patients, patient families and healthcare systems across the globe. While there are conventional approaches to their treatment and management, the beliefs around their development and prognosis continue to present hurdles in the sole use of Western medicine. Complementary and alternative medicinal (CAM) approach, which draws on patients’ cultural beliefs, has been recommended across literature to augment the conventional medicine. This narrative review examined the culturally appropriate interventions for prevention and treatment of mental health in Saudi Arabia. Four culturally oriented approaches were noted to be effective in preventing and managing mental health problems, including faith-based interventions and practices, traditional healing, herbal medicine, and culturally sensitive cognitive behavioral therapy. Nevertheless, the applications of these interventions often face challenges of inadequate resources and culturally competent among other hurdles, which call for the attention of the Saudi healthcare system administrators for better outcomes.